How do environmental awareness, IT use, and credit access shape the sustainability of Indonesian MSMES? - Hadi Ismanto; Aida Nahar; Silviana Pebruary; Purwo Adi Wibowo; Miftakhussabili Nuril Firdaus (Problems and Perspectives in Management)
This study aims to analyze the influence of environmental awareness, information technology (IT) use, and access to credit as moderators on the sustainability of Indonesia’s micro, small, and medium enterprises (MSMEs). Data were obtained through a survey of 1,374 MSMEs. Sampling was carried out using purposive sampling techniques, targeting MSMEs that had been established for more than 3 years and had received loans from financial institutions. The analysis used the ordinary least square (OLS) regression method to evaluate the relationship between the independent variables and MSME sustainability. The results show that environmental awareness and IT use significantly positively affect MSME sustainability. Credit access was also found to have a significant and positive effect. However, the interaction between credit access, environmental awareness, and IT use resulted in a small but significantly negative effect. This suggests that an excessive increase in credit access might reduce the positive impact of environmental awareness and IT use on MSME sustainability. Overall, this study confirms the importance of environmental awareness and information technology in improving MSME sustainability and highlights the need for proper management of credit access. AcknowledgmentAppreciation is given to the Directorate General of Higher Education, Research and Technology, Ministry of Education, Culture, Research and Technology, which has provided a fundamental research grant with contract number 108/E5/PG.02.00.PL/2024. Acknowledgments are also expressed to higher education service institutions (LLDIKTI) Region 6 and the Institute of Research and Community Services (LPPM) Unisnu Jepara Indonesia, which has supported this research.